2003
DOI: 10.1093/ije/dyg049
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and breast cancer in Denmark

Abstract: During the last quarter of the 20th century academics had the highest risk of breast cancer in Denmark. The size of the social gradient in breast cancer occurrence depended on the measure used. The time trends in social distribution will result in breast cancer becoming more frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
43
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 20 publications
11
43
2
3
Order By: Relevance
“…The social inequality at diagnosis observed in our study contrasts with the increasing risk for breast cancer with increasing education (Danø et al, 2003) and occupational group (Dano et al, 2004) in Denmark. It remains unclear whether the reason for the disparity by risk-group is delay in diagnosis or differing biology of cancers in the groups with less education and income compared with more advantaged groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The social inequality at diagnosis observed in our study contrasts with the increasing risk for breast cancer with increasing education (Danø et al, 2003) and occupational group (Dano et al, 2004) in Denmark. It remains unclear whether the reason for the disparity by risk-group is delay in diagnosis or differing biology of cancers in the groups with less education and income compared with more advantaged groups.…”
Section: Discussioncontrasting
confidence: 99%
“…MS is considered to be more frequent in populations of high socioeconomic status, 12 also believed to be afflicted by increased risk of breast cancer, 47,48 prostate cancer 49 and colon cancer. 50 A recent study found no evidence of a socioeconomic gradient in the occurrence of MS in the Danish population 51 and accordingly, we believe that uncontrolled confounding from factors related to socioeconomic status are unlikely to explain the observed cancer profile in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…An important question is whether these relations are indirect, and due to changes in the prevalence of risk factors associated with education, but which we could not study. (2006) Unlike most causes of death, breast cancer mortality risks have often been higher among women of high socioeconomic status (Faggiano et al, 1997;Heck et al, 1997;Dano et al, 2003Dano et al, , 2004. Some studies, however, found no such association (Lund and Jacobsen, 1991;Faggiano et al, 1997).…”
mentioning
confidence: 99%